Vertebrobasilar insufficiency: challenges of diagnosis and treatment - P. R. Kamchatnov (Медицинский совет, 2013)
Vertebrobasilar insufficiency (according to ICD Х, syndrome of vertebrobasilar arterial system, section G45.0, class V "Vascular diseases of the nervous system") is quite a common syndrome that requires from physicians to understand its causes, differential diagnosis and choice of the most suitable treatment.